Present status and problem confrontation of Dyke vegetable production at freshwater ghers of Bagerhat district in Bangladesh (Research in Agriculture Livestock and Fisheries, 2019)
The water-bodies of shrimp/prawn farm are known as “gher” and the embankments of the gher are known as “Dyke”. Recently, vegetable production on the Dykes is gaining popularity in the southwest coastal region. The main purpose of the study was to identify the present status of Dyke Vegetable Production (DVP) in gher and to determine the problem confrontation associated with DVP. Data were collected from randomly selected 84 respondents (50% out of 168 gher owners) of five selected villages of Mollarhat upazila under Bagerhat district, through face-to-face interview using a pre-tested interview schedule during February to April, 2018. Collected data were analyzed by using SPSS software for different statistical techniques and for obtaining results and subsequent interpretation for satisfying the mentioned purpose of the study.Most (86.9%) of the respondents had medium to large sized Dykes, and thus the respondents could bring their Dyke area under vegetables cultivation instead of keeping fallow year after year. The gher owners harvested on an average 218.47 kg vegetable and earned 3,383.807 Tk. annually from one decimal Dyke area which is an additional income. The gher owners who have large sized Dyke in ghers continued production due to high quantity of cumulative profit. About half (51.19%) of the respondents grown lady’s finger in the Dykes during lean period followed by brinjal (48.81%) and tomato (47.61%). The respondents produced 53,962.09 kg ha-1 which is completely extra production contributing to food security. A number of 29 problems were identified as confronted by Dyke vegetables growers with different extent of severity. The most severe problem in Dyke vegetable farming in the study area was “lack of technical knowledge for identification of diseases”. Most of the respondents (96.4%) belonged to medium problem confrontation category. Among 13 selected characteristics of the respondents only annual family income showed a significant positive relationship and extension contact showed a negative significant relationship with the problem confrontation. The gher owners confront medium problems and appropriate measures should be undertaken to reduce these problems as minimum as possible.Res. Agric., Livest. Fish.6(1): 69-78, April 2019